If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-87) = 56 Multiply -1 * -87 x + 87 = 56 Reorder the terms: 87 + x = 56 Solving 87 + x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-87' to each side of the equation. 87 + -87 + x = 56 + -87 Combine like terms: 87 + -87 = 0 0 + x = 56 + -87 x = 56 + -87 Combine like terms: 56 + -87 = -31 x = -31 Simplifying x = -31
| (2x+71)=90 | | 3x-5=2+14 | | (x-4)+72=90 | | 4x^2+29=-28x | | 2x-1=7x+3 | | (2x+17)=90 | | 5y-12-y=0 | | -39-7n=-5+2(-8n-8) | | x-(-14)=-39 | | (x-5)+29=90 | | (8a^-9)^2/3 | | 12=1.5timesp | | -2(t-4)-5= | | (2x+5y)+(x+y)=4+1 | | x^3-9x^2+24x-15=0 | | pq+5q+2p+10= | | x-(-53)=30 | | -3(17q)= | | 912*13/81 | | (x+7)+43=90 | | x^2+20=-12 | | -14x-20=12x+7 | | 3n+4(-4n+1)=2n+4 | | 2m^2+2m-18=0 | | 4x^2+57=28 | | 3(17q)= | | 36m*36m+20m-16= | | (-4)+x=69 | | 9(x+8)-6(x-3)+14=5(x-3)+11 | | -3.5n=2.51 | | B^2+8b=64 | | 3x^2+60=24x |